2021
DOI: 10.3390/molecules27010079
|View full text |Cite
|
Sign up to set email alerts
|

Transgelin-2 in Multiple Myeloma: A New Marker of Renal Impairment?

Abstract: Transgelin is a 22-kDa protein involved in cytoskeletal organization and expressed in smooth muscle tissue. According to animal studies, it is a potential mediator of kidney injury and fibrosis, and moreover, its role in tumorigenesis is emerging in a variety of cancers. The study included 126 ambulatory patients with multiple myeloma (MM). Serum transgelin-2 concentrations were measured by enzyme-linked immunoassay. We evaluated associations between baseline transgelin and kidney function (serum creatinine, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Woziwodzka et al [18] conducted a prospective observational study included 126 patients with MM. A total of 73 women and 53 men were included, aged 29 to 90 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Woziwodzka et al [18] conducted a prospective observational study included 126 patients with MM. A total of 73 women and 53 men were included, aged 29 to 90 years.…”
Section: Discussionmentioning
confidence: 99%
“…Woziwodzka et al [18] highlighted that Symptomatic MM was diagnosed in 119 patients, the majority of whom were in ISS stage I 84 (67%), stage II 20 (16%), stage III 15 (12%). The remaining seven patients had smouldering MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that transgelin-2 has a significant role in lung function in COVID-19 patients. However, transgelin-2 cannot be a COVID-19 prognostic biomarker because its high levels are also associated with other diseases such as asthma, type 2 diabetes, or cancer [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The focus on timely diagnosis and prevention of organ damage drives the interest in diagnostic and prognostic biomarkers. In theory, a validated biomarker can act as a surrogate of underlying disease pathways and inform the physician on the alterations in organ-specific processes; for example, our previous studies demonstrated that urinary insulin growth factor binding protein 7 (IGFBP-7), neutrophil gelatinase-associated lipocalin (NGAL) monomer, and transgelin-2 may be markers of renal impairment in patients with MM [ 3 , 4 ]. The use of appropriate biomarkers may be crucial for adequate tailoring of the treatment plan.…”
Section: Introductionmentioning
confidence: 99%